Association between use of oral-antidiabetic drugs and the risk of aortic aneurysm: a nested case–control analysis. Issue 1 (December 2016) - Hsu, Chien-Yi; Su, Yu-Wen; Chen, Yung-Tai; Tsai, Shih-Hung; Chang, Chun-Chin; Li, Szu-Yuan; Huang, Po-Hsun; Chen, Jaw-Wen; Lin, Shing-Jong
Abstract Background Pleiotropic effects on cardiovascular protection have been suggested in several oral antidiabetic drugs (OAD). The impacts of OADs on aortic aneurysm (AA) growth have been found in animal studies, but the evidence of their beneficial effects for AA protection in human are lacking. We investigated the relationship between OAD therapy and the risk of developing AA. Methods We conducted a nested case–control analysis using the database extracted from Taiwan's National Health Insurance Research Database. The database consists of 1.2 million diabetic patients representing the majority of the type 2 diabetes population in Taiwan from 2000 to 2013. Cases were identified as those with either inpatient or outpatient diagnosis code of AA. One control was selected for each case matching on duration of follow-up, age, sex, urbanization, monthly income, severity of diabetes, and risk factor for AA. We identified variable classes of OADs, including metformin, sulfonylureas, thiazolidinedione (TZD), alpha-glucosidase inhibitors, meglitinide, dipeptidyl peptidase-4 (DPP-4) inhibitors prior to the development of AA. Results A total of 4468 cases diagnosed with AA and 4468 matched controls were identified. Metformin use, sulfonylurea use, and TZD were associated with lower risk of developing AA, odds ratio [OR] 0.72 (95 % confidence interval [CI] 0.64–0.80), 0.82 (95 % CI 0.74–0.92), and 0.82 (95 % CI 0.69–0.98), respectively. The effects of metformin and sulfonylurea on AA were dose responsive. Neither alpha-glucosidase inhibitors (OR 0.95; 95 % CI 0.81–1.11) nor DPP-4 inhibitors (OR 0.85; 95 % CI 0.68–1.07) was significantly associated with AA events. Conclusions Metformin, sulfonylurea, and TZD treated patients were associated with lower risks of AA development, but not DPP-4 inhibitors or alpha-glucosidase inhibitor. The protective effects of hypoglycemic agents are further confirmed by the dose responsive relations in metformin and sulfonylurea groups.